Occipital Nerve Blocks in the Emergency Department for Initial Medication-Refractory Acute Occipital Migraines - Yanuck, Justin (Clin Pract Cases Emerg Med, 2019)
Migraines are consistently among the top 20 primary coded diagnoses in emergency departments, constituting 4.5% of all chief complaints. In a significant subset of these, pain arises from the occipital region innervated by the greater (GON) and lesser occipital nerve. In this case series, we present three patients with occipital migraines who received GON blockade with 1% lidocaine. The blockade was performed only after first-line treatment with metoclopramide and possibly additional medications as ordered by triage physician, failed to adequately alleviate pain by 40 minutes after medication administration. Patients were contacted a minimum of seven days following treatment. All three patients experienced significant analgesia and relief of symptoms within 15 minutes of blockade and sustained relief through a seven-day follow-up period.